Embedded caissons : an exploration of a novel land reclamation method without infill in Changi, Singapore - Tio, Jasper (Nanyang Technological University, 2020)
The rise in sea levels poses a very imminent threat to Singapore’s survival. Singapore’s Prime Minister has been considering land reclamation as one strategy to adapt to the rise in sea levels. Traditional land reclamation uses a substantial amount of sand as infill and with the increasing scarcity of sand, prices have gone up. Thus, there is a need to explore novel reclamation methods that eradicates the use of infill sand. The study explores the feasibility of a land reclamation without infill using caissons in Changi. To investigate the geotechnical feasibility of the method, simulations using PLAXIS 3D were carried out. The economic analysis was carried out by a cost estimate from the extrapolation of costs found using other land reclamation projects. The study focuses on 3 cases, a free-standing embedded caisson, caisson with support structure, and caisson supported on a foundation. The effects of the dewatering process and consolidation were observed through analysis of the resultant stresses and displacements. Results from the analysis have shown that the caissons in the 3 cases are stable throughout the entire construction process, given the appropriate depth of embedment. Consolidation does not have a substantial effect on the stability of the caissons. Seepage is also negligible cause of the low permeability of the soils in Changi. The cost analysis suggests that all three methods proposed by the study are significantly cheaper than traditional land reclamation methods. However, the study focuses primarily on the geotechnical feasibility of these methods. Thus, the study recommends that further studies should be done regarding the feasibility of the support structure as well as the construction and installation of the caisson if the project were to be carried out.